Determinants of flight delays at East Asian airports from an airport, route and network perspective. (July 2021) - Chen, Yun-Hsuan; Lin, Jen-Jia
Abstract: Previous studies on determinants of flight delays have been limited to the attributes of departure and arrival airports and routes and experiences in North America and Europe. This research extends the existing discussions by considering a network perspective to explore East Asian airports. A total of 4611 routes among 318 airports in the second half of 2017 are analyzed using panel data regressions. Results show that the attributes of airports and routes linked with the departure and arrival airports of a flight are the essential determinants of flight delays in East Asia. However, the congestion internalization and hubness effect of departure and arrival airports suggested in previous research are not observed in this region. The associations of slot control levels and route attributes with delays are varying between airports inside and outside China and domestic and international routes. This research supplements a new perspective to understand the determinants of flight delays in existing literature and provides a rarely observed knowledge to encourage East Asian airport operators and carriers developing management strategies for minimizing flight delays. Highlights: The attributes of airports and routes linked with the departure and arrival airports of are essential determinants of flight delays. The congestion internalization and hubness effect of departure and arrival airports not observed in East Asia. The associations of slot control levels and route attributes with delays are varying with airports and routes.